Morphology of abdominal pain: the inside story; investigation of abdominal pain and its correlation with endoscopy and H. pylori status - Saxena, M. K.; Rana, Rooman Ahmad; Gupta, Ashutosh; Ahmad, Ausaf (International Surgery Journal, 2019)
Background: Pain in the abdomen especially upper abdomen is a common presentation in any clinicians OPD. It has a significant effect on the quality of life of the individual. Moreover, it is essential to exclude presence of H. pylori infection since it is known to have carcinogenic effect, as well as the propensity to develop duodenal ulcer. This study was undertaken to understand the association of the above-mentioned symptoms with endoscopic findings and with H. pylori infection, and to find out if there is significant correlation between the above-mentioned symptoms and presence or absence of H. pylori infection. Methods: This is a retrospective descriptive study based on the upper GI endoscopies carried out in the institution. The period covered was from 01 January 2018 to 31 December 2018. The inclusion and exclusion criteria were well defined. Data on patients presenting with symptoms of Gastritis, dyspepsia, epigastric pain and upper abdomen pain was studied. Results: The study showed association between age and H. pylori infection though it was not found to be statistically significant. The association between significant endoscopic finding and H. pylori was statistically significant (p>0.05) epigastric pain as a symptom was found to have strong Statistical significance with presence of H. pylori (p<0.05). Conclusions: Patients presenting with the symptoms of Gastritis, dyspepsia, epigastric pain and upper abdomen pain be investigated and endoscopy and biopsy for H. pylori should be part of protocol for their management.